Antifeedant and insecticidal activity of four medicinal plants from arid regions on adults of the red flour beetle Tribolium castaneum (Coleoptera, Tenebrionidae) - Attafi, Mouna; Demnati, Fatma Allache; Adjal, Fatima; Laimeche, Wafa (Journal of Plant Protection Research, 2026)
Antifeedant and insecticidal activity of four medicinal plants from arid regions on adults of the red flour beetle Tribolium castaneum (Coleoptera, Tenebrionidae)